A homeschool‐based cognitive behavioral program to improve adolescent mental health. Issue 2 (23rd December 2021) - Harper, Amanda; Brewer, Tracy L.
Abstract: Problem: Anxiety and depression are prevalent in the adolescent population and can have significant consequences. Treatment recommendations are established but rates of utilization remain low, often due to a lack of access to mental health providers. Availability of mental health services in a school‐based setting may increase access, but homeschooled children do not have access to these services. Additionally, the COVID‐19 pandemic has increased the number of homeschooled children and compounded the problem of adolescent mental health disorders. Methods: This pilot evidence‐based practice project aimed to increase access to cognitive behavioral therapy (CBT) in adolescents. Eight students from a local homeschool cooperative participated in the Creating Opportunities for Personal Empowerment (COPE) program. A Friedman test was used to evaluate median differences on anxiety and depression screening instruments at baseline, program completion, and 1 month after the program. Students also completed an adapted COPE program evaluation. Results: Median scores on screening instruments decreased from pre‐COPE to 1 month after, although results were not statistically significant. Students reported that the COPE program was helpful, and they learned new ways to deal with their thoughts, feelings, and behaviors. Conclusion: COPE is a feasible option to increase access to CBT in a homeschool setting.